PENGARUH PENDIDIKAN KESEHATAN DENGAN MEDIA VIDEO TENTANG SPINAL ANESTESI TERHADAP TINGKAT KECEMASAN PASIEN YANG AKAN DILAKUKAN TINDAKAN OPERASI SPINAL ANESTESI - Arvin Wahyu Hartanto; Reko Priyonggo; Kaslinda Nur Umifa; Amin Zakaria (Jurnal Kesehatan Hesti Wira Sakti, 2024)
Introduction: Surgery involves invasive procedures using anesthesia, this can cause anxiety and fear in patients and their families. Anesthesia aims to relieve pain, fear and discomfort so that patients feel more comfortable during medical procedures. Pre-operative preparation is very important to ensure the patient's physical and psychological condition is ready to undergo anesthesia and surgical procedures. More than 50% of pre-operative patients experience anxiety worldwide, with 5-25% of them over the age of 20 years. In Indonesia, around 11.6% of the population experiences anxiety. Anxiety can cause delays in surgery, lengthen recovery time, and increase the risk of complications. Health education through videos about spinal anesthesia is considered an effective method because it can be done anytime and anywhere, and can increase patient knowledge and skills. The aim of this study was to analyze the effect of patient education using spinal anesthesia training videos on reducing anxiety levels. Methods: Prae experimental research design, one group pre-post test design, in the population of patients admitted via outpatient who will undergo surgery with spinal anesthesia totaling 30 respondents, the research was carried out in the waiting room of the operating room within a two week research period. Independent variable: provision of health education using video media about spinal anesthesia. Dependent variable: anxiety level. Data were collected using the observation method, carried out pre and post providing health education using video media about spinal anesthesia. The instrument uses The Amsterdam Preoperative Anxiety and Information Scale (APAIS) and is recorded on an observation sheet. Bivariate data analysis, namely by using the Independent T-Test of data, was carried out to determine the difference in the average value of anxiety levels between pre and post treatment, and the data obtained was processed using the SPSS 22 computer application. Results: Hypothesis testing, the significance value is 0.000, which is 0.000. which is less than 0.05. Conclusion: therefore the decision made for this test is that providing health education using video media about spinal anesthesia has an effect on reducing the anxiety level of patients who will undergo surgery with spinal anesthesia and the effect is very strong.  Keywords: Video Media, Health Education, Spinal Anesthesia, Anxiety Level.